Mg-doping towards enhancing the composition-phase-structural stability of Li-La-zirconate based cubic garnet upon exposure to air. (15th March 2019) - Amardeep,; Kobi, Sushobhan; Mukhopadhyay, Amartya
Abstract: Mg, as a new dopant, has been found to stabilize the desired cubic garnet structure ( Ia 3 ¯ d ) of Li-La-zirconate (LLZO) and lead to Li-ion conductivities similar to those obtained with the same level of Al-doping. More importantly, Mg-doping, as opposed to Al-doping, suppresses the deleterious reactions with the atmospheric moisture/CO2, leading to stability in the composition-phase-structure upon exposure to air. Accordingly, when exposed to air, even though Al-doped LLZO pellets get spontaneously fractured/disintegrated, accompanied by reduction in ionic conductivity by 3 orders of magnitude, Mg-doped LLZO shows no sign of cracking and almost retains the ionic conductivity measured prior to exposure. Graphical abstract: Unlabelled Image